1999
DOI: 10.1046/j.1432-1327.1999.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of premature retinoic acid synthesis in Xenopus embryos following premature expression of aldehyde dehydrogenase ALDH1

Abstract: In order for nuclear retinoic acid receptors to mediate retinoid signaling, the ligand retinoic acid must first be produced from its vitamin A precursor retinal. Biochemical studies have shown that retinal can be metabolized in vitro to retinoic acid by members of the aldehyde dehydrogenase enzyme family, including ALDH1. Here we describe the first direct evidence that ALDH1 plays a physiological role in retinoic acid synthesis by analysis of retinoid signaling in Xenopus embryos, which have plentiful stores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…These results clearly show that the EtOHdependent reduction in RA signaling can be rescued by Raldh2 overexpression by providing a high enough enzyme concentration for both EtOH detoxification and RA biosynthesis. Overexpression of Aldh1 has been shown to promote premature activation of RA signaling in the embryo by oxidizing the available RAL (Ang and Duester, 1999b). This observation suggested that ALDH1 could fulfill the enzymatic function of RALDH2 in the early embryo.…”
Section: Disease Models and Mechanisms 297mentioning
confidence: 98%
“…These results clearly show that the EtOHdependent reduction in RA signaling can be rescued by Raldh2 overexpression by providing a high enough enzyme concentration for both EtOH detoxification and RA biosynthesis. Overexpression of Aldh1 has been shown to promote premature activation of RA signaling in the embryo by oxidizing the available RAL (Ang and Duester, 1999b). This observation suggested that ALDH1 could fulfill the enzymatic function of RALDH2 in the early embryo.…”
Section: Disease Models and Mechanisms 297mentioning
confidence: 98%
“…Studies on the second step of RA synthesis, oxidation of retinal to RA, have yielded consistent results indicating that three forms of cytosolic aldehyde dehydrogenase referred to as retinaldehyde dehydrogenase (RALDH) participate in RA synthesis (1). In vitro activities are reported for RALDH1 (4), RALDH2 (5-7), and RALDH3 (8), plus in vivo activities are reported for RALDH1 and RALDH2 (9,10). Gene disruption studies demonstrate that RALDH2 is essential for catalyzing the second step of RA synthesis during development as Raldh2 Ϫ/Ϫ embryos die at mid-gestation and almost totally lack RA (11,12).…”
mentioning
confidence: 94%
“…Instead, the RA molecule is inactivated in several locations by different enzymes. These enzyme types have been demonstrated to play an essential role in retinoid signaling and show discrete domains of expression during embryonic development (Ang and Duester, 1999;Haselbeck et al, 1999;Schneider et al, 2001). …”
Section: Introductionmentioning
confidence: 99%